Increasing Students’ Learning English Outcomes by Using Numbered Head Together (NHT) Model - Mujahidah; Nurul Khalifah Rusni (Institut Agama Islam Negeri Parepare, 2021)
The cooperative learning method Numbered Head Together (NHT) is a learning method based on constructivist learning theory. Numbered Heads Together (NHT) is a structured approach to collaborative learning proposed by Spencer Kagan et al. (Ibrahim, 2000: 25). The aims of this study is to find out the implementation of the Numbered Head Together model to improve students learning outcomes at SMA 4 PAREPARE. This study used a quantitative method. Using a Pre-experimental research design, a class pretest and posttest. Pre- experimental study design was employed to measure changes in outcomes before and after the intervention was put into place. The data is to explain the implementation of Numbered Head Together (NHT) used. Location This research was conducted at UPT SMAN 4 PAREPARE, district Ujung, the city of Parepare. This research focuses on class XI IPS 2 in the odd semester of the 2020/2021 academic year. Class XI IPS 2 contains 31 students, 16 male and 15 female. Base on the results of the research that has been done and the discussion, it can be concluded that; the application of The Numbered Head Together (NHT) learning model on cognitive aspects. This is evidenced by an increase in the value of pretest with an average of 70% increasing to 80.58% in posttest. The percentage of learning completeness also increased from the pretest by 67.74%. Increase to 83.87%. In posttest.